2014
DOI: 10.1039/c4dt00577e
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable chemosensor for oxalate based on bimetallic complexes of a dinucleating bis(iminopyridine) ligand

Abstract: Herein we describe bimetallic di-nickel and di-copper complexes [Ni2(L)Br4] (1) and [Cu2(L)Br4(NCMe)2] (2) (L = (1E,1'E)-N,N'-(1,4-phenylenebis(methylene))bis(1-(6-(2,4,6-triisopropylphenyl)pyridin-2-yl)methanimine)) that bind oxalate intramolecularly to form [Ni2(L)Br2(C2O4)(NCMe)] (3) and [Cu2(L)Br2(C2O4)] (4). For the di-nickel complex 1, oxalate incorporation is accompanied by a significant colour change, from red-pink (1) to deep green (3). Mass spectrometric experiments demonstrate that the compound 1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Tetrabutylammonium oxalate was independently synthesized, and the 13 C­{ 1 H} NMR spectrum of the synthesized oxalate was used to confirm that oxalate was not present in any of the bulk electrolyses (Figures S20 and S21). When water (0.98 M) was included in the electrochemical cell, the bulk electrolysis current was decreased compared to that of the anhydrous reactions, consistent with the cyclic voltammetry experiments. When the headspace was analyzed by gas chromatography, carbon monoxide was observed at low faradaic efficiencies (35%), and hydrogen was also observed (47% faradaic efficiency).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Tetrabutylammonium oxalate was independently synthesized, and the 13 C­{ 1 H} NMR spectrum of the synthesized oxalate was used to confirm that oxalate was not present in any of the bulk electrolyses (Figures S20 and S21). When water (0.98 M) was included in the electrochemical cell, the bulk electrolysis current was decreased compared to that of the anhydrous reactions, consistent with the cyclic voltammetry experiments. When the headspace was analyzed by gas chromatography, carbon monoxide was observed at low faradaic efficiencies (35%), and hydrogen was also observed (47% faradaic efficiency).…”
Section: Resultssupporting
confidence: 76%
“…Calibration curves for carbon monoxide and hydrogen were created by injecting known quantities of CO or H 2 into the electrochemical cell and then sampling the headspace (see Figures S22 and S23 of the Supporting Information). Tetrabutylammonium oxalate was synthesized as described in literature reports, and spectral data matched literature values. , …”
Section: Experimental Sectionmentioning
confidence: 94%
“…Again, the slow kinetics associated with Ni 2+ precluded an appropriate study of the corresponding complexes. The ESI-MS technique allows the detection in a solution of species at low concentration, and this makes it attractive to analyze complexation processes . This confirmed the formation of deprotonated complex species even at acidic pH regions.…”
Section: Resultsmentioning
confidence: 68%
“…[27][28] Using a supramolecular approach, there has been an immense interest in developing efficient chemical sensors for oxalate by colorimetric and fluorescence methods. [29][30][31][32][33][34][35][36][37][38][39][40][41] Previous studies demonstrated that the complexes of certain metal ions including zinc, [32][33] copper, [34][35][36][37][38][39] nickel, [40][41] and calcium [42] can be used as suitable chemosensors for detecting an oxalate anion in solution.…”
Section: Introductionmentioning
confidence: 99%